Oxidative Esterification of Aromatic Aldehydes Using Polymer-Supported Green Bromine - Sridhar, A.; Swarnalakshmi, S.; Selvaraj, M. (Synlett, 2016)
A facile one-pot green chemical conversion of aromatic aldehydes to alkyl esters is described using polymer-supported bromine chloride resin in the presence of potassium carbonate at room temperature. This eco-friendly methodology with simple workup procedure and recovery and recyclability of the resin makes the transformation simple and efficient.
Keywords: bromine chloride resin; esterification; oxidation; aldehyde; hypobromite ion